An analysis conflict of the main character in brave the wild wind novel - Janggur, Oktavianus; Jayantini, I Gusti Agung Sri Rwa; Pratiwi, Desak Putu Eka (Institut Pariwisata dan Bisnis Internasional, 2022)
This study aims to find various types of conflict faced by the main character and the source of the conflict to analyze how the main character's strategy in resolving the conflict is. The data of this research is taken from the novel Brave the Wild Wind. This study focuses more on explaining personal conflicts and cultural conflicts that have been carried out by the main character. The presentation and description of the analyzed characters consist of conflict sources and conflict solutions. The results of this study indicate that the main character faces three conflicts, namely personal, cultural, and social conflicts. Sources of conflict from the main character are wrong perceptions with other parties, inappropriate goals, and undirected relationships. The solutions used by the main character to resolve conflicts are creativity, integration, approach, and cooperation.